Abundance of Two Pelagibacter ubique Bacteriophage Genotypes along a Latitudinal Transect in the North and South Atlantic Oceans - Eggleston, Erin M.; Hewson, Ian (Frontiers in Microbiology, 2016)
This study characterizes viral and bacterial dynamics along a latitudinal transect in the Atlantic Ocean from approximately 10N to 40S. Overall viral abundance decreased with depth, on average there were 1.64 ± 0.71 x107 virus like particles (VLPs) in surface waters, decreasing to an average of 6.50 ± 2.26 x105 VLPs in Antarctic Bottom Water. This decrease was highly correlated to bacterial abundance. There are six major water masses in the Southern Tropical Atlantic Ocean, and inclusion of water mass, temperature and salinity variables explained a majority of the variation in total viral abundance. Recent discovery of phages infecting bacteria of the SAR11 clade of Alphaproteobacteria (i.e. pelagiphages) leads to intriguing questions about the roles they play in shaping epipelagic communities. Viral-size fraction DNA from epipelagic water was used to quantify the abundance of two pelagiphages, using pelagiphage-specific quantitative PCR primers and probes along the transect. We found that HTVC010P, a member of a podoviridae sub-family, was most abundant in surface waters. Copy numbers ranged from an average of 1.03 ± 2.38 x 105 copies ml-1 in surface waters, to 5.79 ± 2.86 x103 in the deep chlorophyll maximum. HTVC008M, a T4-like myovirus, was present in the deep chlorophyll maximum (5.42±2.8x103 copies ml-1 on average), although it was not as highly abundant as HTVC010P in surface waters (6.05±3.01x103 copies ml-1 on average). Interestingly, HTVC008M was only present at a few of the most southern stations, suggesting latitudinal biogeography of SAR11 phages.